Engagement in Group Psychotherapy Among Marginalized Individuals With Hepatitis C. Issue 3 (2nd July 2016) - Dodd, Zoë; Banga, Claire Ann; Mason, Kate; Meaney, Christopher; Leszcz, Molyn; Sockalingam, Sanjeev
ABSTRACT: This article examines an innovative psychoeducational group model at a community-based hepatitis C treatment program in Toronto, Canada. Group support is increasingly used as part of community-based, interdisciplinary approaches to addressing the complex psychosocial needs and barriers to care of individuals living with and/or undergoing treatment for hepatitis C. This article articulates the theoretical framework and details of one such group model. It also examines group engagement and outcomes using data collected over three group cycles. Psychotherapeutic engagement was higher than might be anticipated for a highly marginalized population. Specifically, group cohesion measures were equivalent or higher compared to norms for other support/psychotherapy groups. This study suggests that individuals with complex psychosocial issues have the ability to engage meaningfully in group therapy.